1995
DOI: 10.5935/0305-7518.19950025
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of nerve thickness assessment in the clinical examination for leprosy

Abstract: Summary The assessment of the thickness of the superficial peripheral nerve trunks to document nerve involvement is an important aspect of clinical examination in case finding for leprosy, and is usually done by trained ' paramedical workers (PMWs). This assessment is subject to variability and has implications on the outcome of the survey. The present study proposes to quantify this variability. In this study, 242 individuals, consisting of 50 neuritic cases, 143 nonneuritic cases of leprosy and 49 normal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Depending upon the leprosy subtype, clinical manifestations include sensory deficit, nerve thickening, hypo-or hyperpigmentation, dry skin, erythema, papules, nodules, and ulceration [22][23][24] . Some of these abnormalities remain after leprosy is cured microbiologically [25][26][27] .…”
mentioning
confidence: 99%
“…Depending upon the leprosy subtype, clinical manifestations include sensory deficit, nerve thickening, hypo-or hyperpigmentation, dry skin, erythema, papules, nodules, and ulceration [22][23][24] . Some of these abnormalities remain after leprosy is cured microbiologically [25][26][27] .…”
mentioning
confidence: 99%
“…Nerve palpation is 'subjective' but it has been shown that it can be done reliably for some nerves. 15,16 However, expertise in nerve palpation and interpretation of findings is usually only available with those routinely palpating nerves, which was the case in every research site.…”
Section: Discussionmentioning
confidence: 99%
“…Thickened nerves were found in a greater proportions of new cases in Ethiopia (ulnar nerve in 68%), [6] where the patients often present late, than in India (ulnar nerve in 23%), [7] where detection is generally much earlier. Reported figures for nerve enlargement in MB and PB patients from Bangladesh are 96% and 86% respectively, [5] whereas in Ethiopia, the corresponding figures were 91% and 76%.…”
Section: Skin Lesions With Sensory Impairment Skin Lesions With Sensomentioning
confidence: 95%